Governança de redes sociais para o desenvolvimento sustentável local: análise de fóruns de agenda 21 locais em quatro municípios do Rio Grande do Sul - Padilha, Lívia Garcez de Oliveira (Universidade do Vale do Rio dos Sinos, 2012)
The challenges to meet global sustainability permeate actions at the local level. However, there are difficulties in coordinating different social actors so they can achieve common goals in support of local sustainable development. Agenda 21 is an example of a project that, among other things, provides for the establishment of a social network, called Agenda 21 Forum at the local level. The present dissertation theme treats the governance of social networks for the local sustainable development. The main objective is to understand the constructs that characterize this governance of social networks of Agenda 21 Local Boards from Rio Grande do Sul. In its theoretical foundation the study addresses issues such as: local sustainable development, networks and governance. As a qualitative-quantitative investigation with an exploratory character, the study used Social Network Analysis - ARS, observation techniques, semi-structured interviews and documentary analysis. The empirical phenomena of the investigation were four social networks, Local Boards of Agenda 21 formed by the cities of São Lourenço do Sul, Gravataí, Ijuí and Vacaria, all located in Rio Grande do Sul. Among the study results are a set of constructs formed by: interests, common goals, alignment, rules, engagement, resources, communication, density and centralization. It is believed that the set of constructs of governance might facilitate the achievement of common goals, whether they are specific results of the Local Agenda 21, or other social network. The identification of the constructs had a contribution in the theoretical field, as the approach to governance of social networks is a new theme and still little explored in academic circles. This analysis of the characteristics of governance may assist other social networks to have more opportunities and learn from each other. Thus, with the constructs was possible to advance and bring a preposition of good practices that concern the interaction between actors in social networks
Keywords: Governança; Redes sociais; Desenvolvimento sustentável local; Agenda 21; Governance; Social networks; Local sustainable development; ACCNPQ::Ciências Humanas::Sociologia